Evaluating the impact of visceral fat on the outcomes of frozen embryo transfer via bioelectrical impedance analysis - Ni, Danyu; Wei, Yi; Xie, Qijun; Wang, Xinyu; Yu, Kaidi; Jiang, Wei; Yang, Ye; Ling, Xiufeng (Frontiers in Endocrinology, 2025)
ObjectivesThe increasing prevalence of obesity underscores the need to explore its impact on assisted reproductive technology (ART) outcomes. This study aims to evaluate the association between visceral fat area (VFA), measured by bioelectrical impedance analysis (BIA), and pregnancy outcomes following frozen embryo transfer (FET).MethodsIn this retrospective clinical study, the data of 1,510 patients who underwent FET between April 2022 and April 2023 were analyzed. The VFA was measured by BIA, and patients were categorized into low and high VFA groups based on a threshold of 65 cm². Pregnancy outcomes were compared between the two groups. Univariable and multivariate logistic regression analyses, along with restricted cubic spline (RCS) modeling, were used to adjust for age, body mass index (BMI), and basal estradiol (E2) levels to determine the relationship between VFA and FET outcomes.ResultsThere were significant differences in baseline characteristics and outcomes between the two groups. The high VFA group was characterized by older age and a lower basal estradiol (E2) level. The biochemical pregnancy rate, implantation rate, clinical pregnancy rate (CPR), and live birth rate (LBR) were significantly lower in the high VFA group. Logistic regression revealed a significant negative correlation between the high VFA group and both CPR and LBR. The RCS model demonstrated that the VFA was nonlinearly correlated with CPR and LBR. Subgroup analysis showed that among individuals under 35 years of age or with a BMI < 24, high VFA was significantly associated with poorer CPR and LBR.ConclusionsHigh VFA is associated with poorer pregnancy outcomes after FET in female patients with infertility, with both CPR and LBR decreasing as VFA increases. Clinicians should consider VFA as an important reference for targeted fat management interventions to optimize reproductive success, especially when VFA exceeds 65 cm².